History of special education - Rotatori, Anthony F.; Obiakor, Festus E.; Bakken, Jeffrey P. (Bingley, U.K. : Emerald, 2011)
This volume will examine the history of special education by categorical areas (e.g., Learning Disabilities, Mental Retardation, Autistic Spectrum Disorders). Each categorical area chapter will include an examination of: changing definitions, early pioneers in the field, major contributors and their theoretical ideas, changing educational and treatment practices, working with families, the use of technology, assessment practices and legislative acts specific to that categorical area. The volume will also include chapters on the changing philosophy related to educating students with exceptionalities as well as a detailed history of legal and legislation content concerned with special education. The volume will provide readers with a unique perspective on why special education is what it is today.
ch. 1. Historical and philosophical changes in the education of students with exceptionalities / Spencer J. Salend, Laurel M. Garrick Duhaney -- ch. 2. History of legal and legislative acts concerned with special education / Betty Y. Ashbaker -- ch. 3. History of early childhood special education / Sharon Doubet, Amanda C. Quesenberry -- ch. 4. History of learning disabilities / Carrie Anna Courtad, Jeffrey P. Bakken -- ch. 5. History of intellectual disabilities / Kagendo Mutua, James Siders, Jeffrey P. Bakken -- ch. 6. History of speech and language impairments / Satasha L. Green, Christine M. Scott -- ch. 7. History of emotional and behavioral disorders / Frederick J. Brigham, Brittany L. Hott -- ch. 8. History of deafness and hearing impairments / C. Jonah Eleweke -- ch. 9. History of visual impairments / Stacy M. Kelly, Christine Clark-Bischke -- ch. 10. History of autism spectrum disorders / Julie A. Deisinger -- ch. 11. The history of physical and health impairments / Barbara M. Fulk, Emily Watts, Jeffrey P. Bakken -- ch. 12. The history of giftedness and talent development / Michelle J. McCollin -- ch. 13. History of traumatic brain injury / Anthony F. Rotatori, Sandy Burkhardt -- ch. 14. History of bilingual special education / Fabiola P. Ehlers-Zavala -- ch. 15. Historical and contemporary contexts, challenges, and prospects in the education of students with exceptionalities / Festus E. Obiakor.
Print version record
Keywords: Education -- Special Education -- General; Teaching of specific groups & persons with special educational needs; Teaching of students with specific learning difficulties needs; Special education